A Condom Distribution Program in the Los Angeles Men's Central Jail: Sheriff Deputies' Attitudes and Opinions. (July 2014) - McCuller, William J.; Harawa, Nina T.
The K6G unit of Los Angeles Men's Central Jail is comprised of males who have sex with males (MSM), whether gay, bisexual, or transgender. Within this unit, condoms are distributed to inmates, one condom per week. The current study was conducted to better understand the experiences and opinions of jail staff as they pertain to the condom distribution program's effectiveness and impact on jail safety and management. A total of 10 staff interviews were conducted with the unit's line staff ( n = 8) and administrative personnel ( n = 2). Findings suggest that despite the contradictory "mixed message" that jail staff felt the program sent, it causes few operational or safety concerns and is perceived to be beneficial to public health.